QTc INTERVAL DURATION CLASS AND DRUG THERAPY OF PATIENCE IN A FIRST YEAR AFTER PACEMAKER IMPLANTATION - Brynza, M. S.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
49 patients (28 female, 21 male) with implanted DDD/DDDR, VVI/VVIR and CRT pacemakers are investigated. Purpose frequency and dose rate of anticoagulants, antiplatelet agents, direct thrombin inhibitors, cardiac glycosides, amiodarone; ivabradine, diuretics, aldosterone antagonists, beta-adrenergic blockers, calcium channel blockers, angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARBs), statins were evaluated before, in acute postoperative period (3–5 days), 6 months and 1 year after pacemaker implantation. Patients were divided into classes 1 (normal QTc (320–440 ms)) – 24 (49 %) patients) and 2 (long QTc (> 440 msec)) – 25 (51 %) patients) of QTc interval duration. To process the data using standard statistical procedures using Microsoft Excel. It was more often prescriptions of new anticoagulants, beta-adrenergic blockers, ARBs, statins to patients in the first year after pacemaker implantation. QTc interval duration lengthening was associated with a greater purpose frequency and doses of amiodarone, diuretics, beta-adrenergic blockers, ACE inhibitors, ARBs and statins. Patients with implanted pacemaker need individualized drug therapy according to QTc interval duration, in particular, enhancing antiischemic, antihypertensive, antiarrhythmic therapy and therapy of chronic heart failure in patients with QTc interval duration lengthening.